A general method for preparing lanthanide oxide nanoparticles via thermal decomposition of lanthanide(III) complexes with 1-hydroxy-2-naphthoic acid and hydrazine ligands. (September 2016) - Parimalagandhi, Karuppannan; Premkumar, Thathan; Vairam, Sundararajan
Abstract: Six new lanthanide(III) complexes (i.e., [Ln(L)2 (NA)1.5 ]·3H2 O, where Ln=La(III), Pr(III), Nd(III), Sm(III), Gd(III), and Ce(III) and L and NA indicate N2 H4 and C10 H6 (1- O)(2- COO), respectively) with 1-hydroxy-2-naphthoic acid [C10 H6 (1- O)(2- COOH)] and hydrazine (N2 H4 ) as co-ligands were characterized by elemental, FTIR, UV-visible, and XRD techniques. In the FT-IR spectra, the N-N stretching frequency in the range of 981–949 cm −1 demonstrates evidence of the presence of coordinated N2 H4, indicating the bidentate bridging nature of hydrazine in the complexes. These complexes show symmetric and asymmetric COO − stretching from 1444 to 1441 cm −1 and 1582 to 1557 cm −1, respectively, indicating bidentate coordination. TG-DTA studies revealed that the compounds underwent endothermic dehydration from 98 to 110 °C. This was followed by the exothermic decomposition of oxalate intermediates to yield the respective metal oxides as the end products. From SEM images, the average size of the metal oxide particles prepared by thermal decomposition of the complexes was determined to be 39–42 nm. The powder X-ray and SEM coupled with energy dispersive X-ray (EDX) studies revealed the presence of the respective nano-sized metal oxides. The kinetic parameters of the decomposition of the complexes were calculated using the Coats-Redfern equation. Highlights: We prepared lanthanide hydrazine 1-hydroxy-2-naphthoate complexes. These complexes underwent thermal decomposition to the respective nano-metal oxides. These complexes act as precursors for the synthesis of nano-sized lanthanide oxides.